Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=6x^4-9x^3+3x^2-4x^3+6x^2-2x+10x^2-15x+5\)
\(=6x^4-13x^3+19x^2-17x+5\)
b: \(=6x^4-\dfrac{9}{4}x^3-\dfrac{9}{2}x^2-\dfrac{8}{3}x^3+x^2+2x-\dfrac{20}{3}x^2+\dfrac{5}{2}x+5\)
\(=6x^4-\dfrac{59}{12}x^3-\dfrac{67}{6}x^2+\dfrac{9}{2}x+5\)
c: \(=3x^4-\dfrac{9}{8}x^3-\dfrac{3}{4}x^2+8x^3-3x^2-6x-\dfrac{4}{3}x^2+\dfrac{1}{2}x+1\)
\(=3x^4-\dfrac{55}{8}x^3-\dfrac{25}{12}x^2-\dfrac{11}{2}x+1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b: Đặt \(x^2-6x-2=a\)
Theo đề, ta có: \(a+\dfrac{14}{a+9}=0\)
=>(a+2)(a+7)=0
\(\Leftrightarrow\left(x^2-6x\right)\left(x^2-6x+5\right)=0\)
=>x(x-6)(x-1)(x-5)=0
hay \(x\in\left\{0;1;6;5\right\}\)
c: \(\Leftrightarrow\dfrac{-8x^2}{3\left(2x-1\right)\left(2x+1\right)}=\dfrac{2x}{3\left(2x-1\right)}-\dfrac{8x+1}{4\left(2x+1\right)}\)
\(\Leftrightarrow-32x^2=8x\left(2x+1\right)-3\left(8x+1\right)\left(2x-1\right)\)
\(\Leftrightarrow-32x^2=16x^2+8x-3\left(16x^2-8x+2x-1\right)\)
\(\Leftrightarrow-48x^2=8x-48x^2+18x+3\)
=>26x=-3
hay x=-3/26
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1: (Sgk/36):
a. \(\dfrac{5y}{7}\)=\(\dfrac{20xy}{28x}\) vì
5y . 28x = 140xy
7 . 20xy = 140xy
=> 5y . 28x = 7 . 20xy
Vậy \(\dfrac{5y}{7}\)=\(\dfrac{20xy}{28x}\)
b. \(\dfrac{3x\left(x+5\right)}{2\left(x+5\right)}\)=\(\dfrac{3x}{2}\) vì
3x . 2(x+5) = 6x2+30x
2 . 3x(x+5) = 6x2+30x
=> 3x . 2(x+5) = 2 . 3x(x+5)
Vậy \(\dfrac{3x\left(x+5\right)}{2\left(x+5\right)}\)=\(\dfrac{3x}{2}\)
c. \(\dfrac{x+2}{x-1}\)=\(\dfrac{\left(x+2\right)\left(x+1\right)}{x^2-1}\) vì
(x+2) (x2-1) = (x+2) (x-1) (x-1)
=> (x+2) (x2-1) = (x-1) (x+2) (x+1)
Vậy \(\dfrac{x+2}{x-1}\)=\(\dfrac{\left(x+2\right)\left(x+1\right)}{x^2-1}\)
d. \(\dfrac{x^2-x-2}{x+1}\)=\(\dfrac{x^2-3x+2}{x-1}\)
(x-1) (x2-x-2) = x3-2x2-x+2
(x+1) (x2-3x+2) = x3-2x2-x+2
=> (x-1) (x2-x-2) = (x2-3x+2) (x+1)
Vậy \(\dfrac{x^2-x-2}{x+1}\)=\(\dfrac{x^2-3x+2}{x-1}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\dfrac{1}{2}x-1\right)\left(2x-3\right)=x^2-\dfrac{3}{2}x-2x+3=x^2-\dfrac{1}{2}x+3\)\(b,\left(x-7\right)\left(x-5\right)=x^2-5x-7x+35=x^2-12x+35\)\(c,\left(x-\dfrac{1}{2}\right)\left(x+\dfrac{1}{2}\right)\left(4x-1\right)=\left(x^2-\dfrac{1}{4}\right)\left(4x-1\right)=4x^3-x^2-x+\dfrac{1}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(C=\dfrac{1}{x+2}+\dfrac{1}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4x+7}{\left(x+2\right)\left(\left(4x+7\right)\right)}+\dfrac{1}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4x+7+1}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4x+8}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4\left(x+2\right)}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4}{4x+7}\)
\(D=\dfrac{1-3x}{2x}+\dfrac{3x-2}{2x-1}+\dfrac{3x-2}{2x-4x^2}\\ D=\dfrac{1-3x}{2x}+\dfrac{3x-2}{2x-1}-\dfrac{3x-2}{4x^2-2x}\\ D=\dfrac{\left(1-3x\right)\left(2x-1\right)}{2x\left(2x-1\right)}+\dfrac{\left(3x-2\right)2x}{\left(2x-1\right)2x}-\dfrac{3x-2}{2x\left(2x-1\right)}\\ C=\dfrac{\left(1-3x\right)\left(2x-1\right)+\left(3x-2\right)2x-\left(3x-2\right)}{2x\left(2x-1\right)}\\ C=\dfrac{\left(1-3x\right)\left(2x-1\right)+\left[\left(3x-2\right)2x-\left(3x-2\right)\right]}{2x\left(2x-1\right)}\\ C=\dfrac{\left(1-3x\right)\left(2x-1\right)+\left(3x-2\right)\left(2x-1\right)}{2x\left(2x-1\right)}\\ C=\dfrac{\left[\left(1-3x\right)+\left(3x-2\right)\right]\left(2x-1\right)}{2x\left(2x-1\right)}\\ C=\dfrac{-\left(2x-1\right)}{2x\left(2x-1\right)}\\ C=-\dfrac{1}{2x}\)
Sửađề: \(\dfrac{1}{x+2}+\dfrac{1}{\left(x+2\right)\left(4x+7\right)}\)
\(=\dfrac{4x+7+1}{\left(x+2\right)\left(4x+7\right)}=\dfrac{4}{4x+7}\)